2016
DOI: 10.1002/ange.201609991
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Permeable Tubular Membrane Reactor: Promoting Conversion and Product Selectivity for Non‐Oxidative Activation of Methane over an Fe©SiO2 Catalyst

Abstract: Non-oxidative methane conversion over FeSiO 2 catalyst was studied for the first time in ah ydrogen (H 2 ) permeable tubular membrane reactor.T he membrane reactor is composed of am ixed ionic-electronic SrCe 0.7 Zr 0.2 Eu 0.1 O 3Àd thin film ( % 20 mm) supported on the outer surface of ao neend capped porous SrCe 0.8 Zr 0.2 O 3Àd tube.Significant improvement in CH 4 conversion was achieved upon H 2 removal from the membrane reactor compared to that in afixed-bed reactor. The FeSiO 2 catalyst in the H 2 permea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 44 publications
3
27
1
Order By: Relevance
“…The recently reported non-oxidative methane conversion to olefins, aromatics and hydrogen (MTOAH) over the single iron sites embedded in a silica matrix (Fe©SiO 2 ) does avoid complete dehydrogenation to coke and over-oxidation to CO 2 , representing an atom-economic transformation process of methane [ 18 , 19 ]. Thereafter, similar single sites of catalysts were reported [20][21][22][23] . For example, Sakbodin et al studied the MTOAH over Fe©SiO 2 in a hydrogen permeable tubular membrane reactor for the first time and 20% methane conversion with 65% C 2 selectivity was obtained at 1303 K for 60 h [20] .…”
supporting
confidence: 72%
See 1 more Smart Citation
“…The recently reported non-oxidative methane conversion to olefins, aromatics and hydrogen (MTOAH) over the single iron sites embedded in a silica matrix (Fe©SiO 2 ) does avoid complete dehydrogenation to coke and over-oxidation to CO 2 , representing an atom-economic transformation process of methane [ 18 , 19 ]. Thereafter, similar single sites of catalysts were reported [20][21][22][23] . For example, Sakbodin et al studied the MTOAH over Fe©SiO 2 in a hydrogen permeable tubular membrane reactor for the first time and 20% methane conversion with 65% C 2 selectivity was obtained at 1303 K for 60 h [20] .…”
supporting
confidence: 72%
“…Thereafter, similar single sites of catalysts were reported [20][21][22][23] . For example, Sakbodin et al studied the MTOAH over Fe©SiO 2 in a hydrogen permeable tubular membrane reactor for the first time and 20% methane conversion with 65% C 2 selectivity was obtained at 1303 K for 60 h [20] . Xie et al also reported that methane can be activated by single-atom Pt dispersed within ceria support (Pt@CeO 2 ) under non-oxidative conditions, achieving 14.4% methane conversion with 74.6% selectivity toward C 2 products at 1248 K [21] .…”
supporting
confidence: 72%
“…In this work, by coupling steam methane reforming with in‐situ H 2 removal in a proton conducting membrane reactor, the coke deposition is expected to be inhibited in the presence of steam on methane side. In fact, when using proton conducting membrane to replace oxygen‐permeable membrane, the reaction on methane side changes from POM to SMR that is more coke‐resistant, and also a mature commercial process. After 100 hr reaction, temperature programmed oxidation (TPO) and thermogravimetric analysis (TGA) were used to characterize the spent catalyst (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…First, methane and water are sent to the feed side of the membrane. At high temperatures, steam methane reforming (SMR) takes place over Ni‐based catalyst packed on the membrane surface, forming syngas with a H 2 /CO ratio of 3 according to CH 4 + H 2 O → 3H 2 + CO. Then, the produced hydrogen molecules can chemically adsorb and dissociate into protons (H + ) on membrane surface, which can be further in‐situ removed as H + to the other side if there is a gradient of hydrogen partial pressure across the dense proton conducting membrane . Meanwhile, the electrons migrate in the same direction to maintain the local charge neutrality.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of Fe@SiO 2 catalyst has further been applied for nonoxidative activation of CH 4 in hydrogen-permeable tubular membrane reactor. 145 By adding H 2 in the feed gas into the membrane reactor, 30% conversion of CH 4 and 99% selectivity to C2 products (acetylene and ethylene) can be achieved with good stability at 1303 K.…”
Section: Catalytic Applications Of Supported Single Atomsmentioning
confidence: 99%